Evil Geniuses: A book review - Barnes, John (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
Evil Geniuses : A book review Kurt Anderson is a best selling author with the following titles to his credit You Can’t Spell America Without Me (co-author) Fantasyland True Believers Reset Heyday Turn of the Century. Anderson has also written for stage and screen. The book comprises five sections divided into twenty-nine chapters. An ever-increasing number of books in the west focus on the income disparity between the few very rich and the many poor in developed western societies. The book under review here adds to those books but focuses on the American political issues which brought the current situation into being.